Islamic Boarding School Marketing Strategy to Increase the Number of New Students at North Darul Rasyid Raman Islamic Boarding School - Rohidin, Rohidin; Nugraha, M.E.K, Denas Hasman (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study examines the marketing strategy implemented by the North Darul Rasyid Raman Islamic Boarding School in increasing the number of new students. The phenomenon of transforming the educational paradigm from a social aspect to a business orientation encourages pesantren to adopt effective marketing strategies. The purpose of the research is to analyze the marketing strategies implemented and identify the supporting and inhibiting factors of their implementation. Using a descriptive qualitative approach, data was collected through observation, interviews with caregivers, administrators, students, and the community, as well as documentation. The results of the study show that the marketing strategies implemented include alumni service programs, social media optimization, the use of external media, the development of superior programs such as Tahfidz Qur'an and Arabic, and increasing the creativity of students. This strategy has proven effective with an increase in the number of students from 100 in 2020 to 500 in 2024. Supporting factors include the completeness of educational facilities from TKIT to SMAIT, while inhibiting factors include limited human resources in digital media management and education cost issues. Strategy evaluation is carried out through periodic meetings and direct monitoring by the head of the Islamic boarding school. The implementation of strategic management includes planning, organizing, mobilizing, and controlling that contribute to increasing public trust.